2011
DOI: 10.1158/0008-5472.can-11-1896
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Dependent Gene Transcription in Human Breast Cancer Cells Relies upon Proteasome-Dependent Monoubiquitination of Histone H2B

Abstract: The estrogen receptor-a (ERa) determines the phenotype of breast cancers where it serves as a positive prognostic indicator. ERa is a well-established target for breast cancer therapy, but strategies to target its function remain of interest to address therapeutic resistance and further improve treatment. Recent findings indicate that proteasome inhibition can regulate estrogen-induced transcription, but how ERa function might be regulated was uncertain. In this study, we investigated the transcriptome-wide ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
215
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(236 citation statements)
references
References 48 publications
21
215
0
Order By: Relevance
“…The fact that Ctr9-dependent expression of genes is involved in actin organization is consistent with a recent report that a PAF1-ERK5-ERα complex plays a role in actin reorganization via regulation of a transcriptional program of ERα in breast cancer (Madak-Erdogan et al 2014). PAFc has been previously shown to facilitate transcription elongation and transcription-coupled histone modifications (Tomson and Arndt 2013), including H2Bub1, which is required for ERα-regulated gene transcription (Prenzel et al 2011). Consistent with these reports, we demonstrated that Ctr9 promotes E2-stimulated transcription initiation by stimulating recruitment of ERα and RNAPII to target promoters and promoting downstream H3K27ac.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that Ctr9-dependent expression of genes is involved in actin organization is consistent with a recent report that a PAF1-ERK5-ERα complex plays a role in actin reorganization via regulation of a transcriptional program of ERα in breast cancer (Madak-Erdogan et al 2014). PAFc has been previously shown to facilitate transcription elongation and transcription-coupled histone modifications (Tomson and Arndt 2013), including H2Bub1, which is required for ERα-regulated gene transcription (Prenzel et al 2011). Consistent with these reports, we demonstrated that Ctr9 promotes E2-stimulated transcription initiation by stimulating recruitment of ERα and RNAPII to target promoters and promoting downstream H3K27ac.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, CDC73 was shown to be WT in benign parathyroid tumours where H2Bub1 levels were maintained (Hahn et al 2012). Furthermore, in breast cancer, basal levels of H2Bub1 were found to be unchanged when comparing normal mammary epithelium with benign breast tumours; however, H2Bub1 levels in malignant and metastatic breast cancer cells were found to be significantly reduced (Prenzel et al 2011). The mechanism of H2Bub1 loss in malignant and metastatic breast cancer, lung cancer and colorectal cancer cells remains to be elucidated.…”
Section: H2bub1 and Associated Machinery In Primary Tumoursmentioning
confidence: 99%
“…Identification of H2Bub1 as a key transcriptional regulator raised the likelihood that it may be altered in cancer development and the possibility that H2Bub1 itself may have tumour-suppressive roles (Espinosa 2008). Loss of global H2Bub1 detected by immunohistochemical staining has been reported for a number of cancers, including breast (Prenzel et al 2011), colorectal (Urasaki et al 2012), lung (Urasaki et al 2012) and parathyroid (Hahn et al 2012). In the case of parathyroid cancer, a mechanistic explanation for the loss of H2Bub1 is provided by the frequent occurrence of mutations in the tumour suppressor CDC73, leading to the disruption of the RNA polymerase II-associated factor 1 (PAF1) transcriptional complex that is important for the regulation of H2Bub1 (Hahn et al 2012).…”
Section: H2bub1 and Associated Machinery In Primary Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of RNF20 results in a decrease in p53 expression and an increase in cell migration and tumorigenesis as well as an increase in expression of c-myc, a proto-oncogene . A tumorsuppressive role for RNF40 mediated through H2Bub1 has also been demonstrated in breast cancer cells (Prenzel et al, 2011).…”
mentioning
confidence: 95%